Genetic Profiling And In Vitro Characterization Of OTX1 Functional Role On Bladder Cancer Stem Cells - Ahmad, Umar Salisu; Yusuf Alhaji, Suleiman; Malami , Sani Abubakar (My University, 2020)
Bladder cancer has the highest cost per patient among all cancers due to the high risk of recurrence and the need for life-long routine monitoring as well as therapy. Cancer stem cells (CSCs) are hypothesised to be linked to long-term recurrence risk due to its ability to repopulate the entire tumour population in a small number of cells. In addition, CSC as according to the stem cell model, has the property of self-renewal. Thus, only CSC has sufficient time to accumulate adequate genetic mutations that drive the acquisition of resistance against chemo- and radiation-therapy leading to initiation of recurrence. Recently, OTX1 has been shown to be involved in the differentiation of breast CSCs into differentiated cancer cells. The gene is also reported to be involved in other cancers such as subset of B cells in aggressive non-Hodgkin lymphomas, lung cancer and most recently in bladder cancer. Although the involvement of OTX1 in cancers is demonstrated by limited number of studies, the gene remains to be an interesting candidate for further investigation. We propose that OTX1 may be responsible for the differentiation of CSC and also promote tumour aggressiveness. We plan to establish the expression and localisation patterns of OTX1 gene for Nigerian bladder cancer patients and correlate with clinical characteristics such as stage and grade; risk of recurrence; disease progression and age. To understand the role of OTX1 in bladder cancer stem cells, the gene will be overexpressed/knockdown in non OTX1expressing and OTX1 expressing CSCs, respectively, and the .resulting,. Phenotypic effects will be compared.
Keywords: Genetic profiling; OTX1; Stem cells